Toxic effects of perfluorinated compounds at human cellular level and on a model vertebrate. (June 2017) - Rainieri, Sandra; Conlledo, Nadia; Langerholc, Tomaž; Madorran, Eneko; Sala, Martin; Barranco, Alejandro
Abstract: This work aims at deepening the understanding of the mode of action of some of the most prominent perfluorinated compounds (PFCs) by detecting in a realistic way their effects. To this end, after adjusting the exposure media taking into account the biological model employed and the physico-chemical properties of PFCs, we evaluated the toxic effects of PFOA, PFOS and PFNA in a human macrophage cell line (TLT cells) and in zebrafish embryos. We performed such evaluation on individual compounds and mixtures. Acute toxicity was greater for PFOS in zebrafish; however, it was greater for PFNA in TLT cells. PFNA was also the compound producing the greatest levels of oxidative stress, both in zebrafish and TLT cells. Additionally, in both biological systems, it showed a much stronger effect on mixtures in comparison to the others PFCs tested in this work. Mixture studies in zebrafish showed that acute toxicity depended on the concentration and that the mixture was far more toxic than the individual compounds. This study highlights the importance of studying PFCs in realistic conditions on various biological models. Highlights: Experimental conditions and media can affect the concentration of PFCs available to the biological system used. To avoid the underestimation of toxic effects it is important to evaluate a variety of end-points in different models. Mixtures of PFCs can have a higher acute toxicity with respect to individual compounds. PFNA showed a greater oxidative stress and a greater influence on mixture toxicity with respect to PFOA and PFOS.